Implantation of a Coronary Stent Into the Canaliculus of a Human Cadaver: A Pilot Study. Issue 4 (6th December 2022) - Daigle, Patrick; Morand, Meggie; Nijhawan, Navdeep
Abstract : Purpose: To evaluate the possibility of implanting a drug-eluting coronary stent into the canaliculus of a human cadaver. Methods: The punctum and canaliculus of an embalmed human cadaver were identified and dilated using a punctum dilator and Bowman probes. At this stage, the integrity of the lacrimal drainage system was assessed by dacryoendoscopy. A drug-eluting coronary stent, which was collapsed around a balloon at the tip of a catheter, was inserted into the canaliculus. The balloon was inflated to expand and lock the spring-like stent into position. The balloon catheter was then deflated and removed from the canaliculus. Dacryoendoscopy was used once again to assess the position of each stent after implantation. Results: The four canaliculi of one human cadaver were successfully identified, dilated, and intubated using drug-eluting coronary stents. Dacryoendoscopy confirmed that each stent achieved a satisfactory position within the canaliculi. The seamless integration of the stent with the surrounding tissues resulted in a significant dilation of the canaliculi. The procedure was deemed short and simple, with the time required to implant a stent into the canaliculus and asses its position being less than a minute. Conclusions: Canalicular obstructions can often be a source of therapeutic challenges. Our pilot study shows that a drug-eluting coronary stent can be implanted with precision into the canaliculus of a human cadaver. We propose that at least some canalicular obstructions could be treated using a novel rigid mesh tube similar to drug-eluting coronary stents. Abstract : Pilot study evaluating the possibility of implanting a drug-eluting coronary stent into the canaliculus of a human cadaver.